Network operating systems making the right choices - Hunter Philip (Wokingham Addison-Wesley, 1994)
This book provides a business perspective on the issues involved in selecting a network operating system, and how it relates to the surrounding information technology issues such as security and systems management.
Keywords: Computer networks-software; Operating systems (Computers)